2022
DOI: 10.26434/chemrxiv-2022-fnfck
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Theory of Protein Charge Transfer: Electron Transfer between Tryptophan Residue and Active Site of Azurin

Abstract: One reaction step in the conductivity relay of azurin, electron transfer between the Cu-based active site and the tryptophan residue, is studied theoretically and by classical molecular dynamics simulations. Oxidation of tryptophan results in electrowetting of this residue. This structural change makes the free energy surfaces of electron transfer non-parabolic as described by the Q-model of electron transfer. We analyze the medium dynamical effect on protein electron transfer produced by coupled Stokes-shift … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 49 publications
2
6
0
Order By: Relevance
“…The average distance between tyrosine's phenol ring and the Cu atom of the active site ⟨R⟩ i changes somewhat between the two states, but the main difference between two electron-transfer states in terms of distance statistics is in the distance variance. Consistently with our previous simulations of wild type azurine [57], the state with a higher number of water molecules around the residue shows a greater extend of distance flexibility. In the present simulations, a larger number of water molecules was found around neutral Tyr (Figure S10), which is reflected by a broader distribution of donor-acceptor distanced (Figure S3) and a larger distance variance (Table 1).…”
Section: Statesupporting
confidence: 91%
See 2 more Smart Citations
“…The average distance between tyrosine's phenol ring and the Cu atom of the active site ⟨R⟩ i changes somewhat between the two states, but the main difference between two electron-transfer states in terms of distance statistics is in the distance variance. Consistently with our previous simulations of wild type azurine [57], the state with a higher number of water molecules around the residue shows a greater extend of distance flexibility. In the present simulations, a larger number of water molecules was found around neutral Tyr (Figure S10), which is reflected by a broader distribution of donor-acceptor distanced (Figure S3) and a larger distance variance (Table 1).…”
Section: Statesupporting
confidence: 91%
“…The present article extends our previous results [57] for intraprotein electron transfer between tryptophan (Trp) residue of azurin and its active site to a single-residue mutation replacing tryptophan with tyrozine (Tyr). The reaction of transferring the hole from Trp to Cu I of the active site was studied experimentally by Shih et al [58] and the reaction time of τ ET ≃ 31 ns reported.…”
Section: !"#supporting
confidence: 76%
See 1 more Smart Citation
“…Molecular dynamics (MD) simulation and theoretical calculations presented in this Letter support this hypothesis. Here and elsewhere 31 we use MD simulations to study the activation parameters of transferring a hole from the tryptophan (Trp + ) cation radical to Cu I active site of azurin 32…”
Section: Toc Graphicmentioning
confidence: 99%
“…MD simulations were set up as described elsewhere 31 and in Supplementary Information (SI). Briefly, azurin protein in two electron-transfer states was solvated with 36469 TIP3P/TIP3P-HW (Table 1) water molecules and the production simulations of 300 ns were done in the NVT ensemble.…”
Section: Toc Graphicmentioning
confidence: 99%